Friends of the Family: Some Miracles for Children by Italian Friars - Webb, Diana M. (Studies in church history, 1994)
At some time in the 1320s, the Sienese master Simone Martini painted an altar-piece celebrating the Hermit friar Agostino Novello. Agostino, who had died at the convent of San Leonardo al Lago, near Siena, in 1309, is shown surrounded by illustrations of four of his posthumous miracles (see plates 1 and 2, pp. 198 and 200, below). Of these, three were performed on behalf of children. The exception, at upper right, shows the deliverance of a knight who, riding in a desolate mountainous landscape, has fallen beneath his horse. Top left, we see the rescue of a child from mauling by what is presumably a wolf. Below, a child falls into the street from a wooden balcony when one of its slats gives way; not only does he suffer no injury from the fall, but Agostino seizes the falling slat in mid-air and prevents it from hurting him. Bottom right, an infant suffers head injuries when he falls from his cradle, but his aunt kneels to make a vow to Agostino, and in the lower register we see the fulfilment of the vow: robed as a little Augustinian friar and carrying a taper, the child is carried by his nurse to give thanks, followed by his mother and his aunt, who carries another taper.